Modos de fazer das alfabetizadoras do Grupo Escolar Padre Mário Forestan - 1958 a 1974 - Oliveira, Geracilda Maria (2018)
This research was constituted by the practices of the literacy teachers of the Father Mário Forestan School Group (GEPMF), from 1958 to 1974, by the theoretical contribution of the New Cultural History that enabled this research and Alberti Oral History methodology. The interviews were very important to the accomplishment of this work, they were the ones that sustained the development of the research, allowing the construction of the history of literacy practices in this school group. In view of this, the interviews provided an understanding of the processes that constituted the practices of literacy teachers, and their representations in the process of teaching reading and writing, as well as the meanings and meanings that underpinned their tasks. Thus, literacy in the GEPMF contributes to the construction of the history of Uberlandian, Minas Gerais and Brazilian literacy The interviews envisioned literacy practices, however, in order to know the process of implantation of the Father Mário Forestan School Group, built in a peripheral district of the city of Uberlândia, the investigation also occurred in the decrees, laws, school regiments and in the various documents found in the own institution, in the Regional Superintendence of Education and in the Public Archive of Uberlândia. The research was organized in three chapters, the first chapter deals with the methodological assumptions of New Cultural History, Oral History, History of School Institutions and History of Literacy. The second chapter describes the history of literacy in the social, political and economic scenario in Brazil, in Minas Gerais and Uberlândia, specifically in the Escola Mário Forestan School Group. The third chapter explores the literacy practices developed in the Father Mário Forestan School Group in dialogue with the Elementary Education Program of the Minas Gerais Education Secretariat.